Repurposing Chloroquine Against Multiple Diseases With Special Attention to SARS-CoV-2 and Associated Toxicity - Kamat, Siya; Kumari, Madhuree (Frontiers in Pharmacology, 2021)
Chloroquine and its derivatives have been used since ages to treat malaria and have also been approved by the FDA to treat autoimmune diseases. The drug employs pH-dependent inhibition of functioning and signalling of the endosome, lysosome and trans-Golgi network, immunomodulatory actions, inhibition of autophagy and interference with receptor binding to treat cancer and many viral diseases. The ongoing pandemic of COVID-19 has brought the whole world on the knees, seeking an urgent hunt for an anti-SARS-CoV-2 drug. Chloroquine has shown to inhibit receptor binding of the viral particles, interferes with their replication and inhibits 'cytokine storm'. Though multiple modes of actions have been employed by chloroquine against multiple diseases, viral diseases can provide an added advantage to establish the anti- SARS-CoV-2 mechanism, the in vitro and in vivo trials against SARS-CoV-2 have yielded mixed results. The toxicological effects and dosage optimization of chloroquine have been studied for many diseases, though it needs a proper evaluation again as chloroquine is also associated with several toxicities. Moreover, the drug is inexpensive and is readily available in many countries. Though much of the hope has been created by chloroquine and its derivatives against multiple diseases, repurposing it against SARS-CoV-2 requires large scale, collaborative, randomized and unbiased clinical trials to avoid false promises. This review summarizes the use and the mechanism of chloroquine against multiple diseases, its side-effects, mechanisms and the different clinical trials ongoing against 'COVID-19'.